2020
DOI: 10.48550/arxiv.2009.08914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Directional association of TeV to PeV astrophysical neutrinos with radio blazars

A. V. Plavin,
Y. Y. Kovalev,
Y. A. Kovalev
et al.

Abstract: We have shown recently that high-energy neutrinos above 200 TeV detected by IceCube are produced within several parsecs in the central regions of radio-bright active galactic nuclei (AGNs). To independently test this result and to extend the analysis to a wider energy range, we use here public data for all energies from seven years of IceCube observations. The IceCube point-source likelyhood map is analyzed against positions of AGNs from a large complete sample selected by their compact radio flux density. The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
1
3
1
Order By: Relevance
“…We simply note that there is no obvious reason to exclude any of the sources as a possible neutrino emitter. This is also in line with the discussion in Plavin et al (2020b). They did not find reasons to disfavor the non γ-ray AGNs as neutrino sources in terms of target photon fields or the accelerated protons.…”
Section: Connection With γ-Ray Emissionsupporting
confidence: 87%
See 2 more Smart Citations
“…We simply note that there is no obvious reason to exclude any of the sources as a possible neutrino emitter. This is also in line with the discussion in Plavin et al (2020b). They did not find reasons to disfavor the non γ-ray AGNs as neutrino sources in terms of target photon fields or the accelerated protons.…”
Section: Connection With γ-Ray Emissionsupporting
confidence: 87%
“…The number of associations we find is in general small, only with 12 − 28% of the 57 neutrino events, depending on the radio sample used. The small number of associations can be largely explained by incomplete parent samples of radio sources used in this study and is not in contradiction with the recent studies of Plavin et al (2020a); Plavin et al (2020b) associating the observed astrophysical neutrino flux to radio bright AGN.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The coincidence of the two highest energy alerts to date with extended periods of radio emission has led to the speculation that all, 67 or at least some, 68 cosmic neutrinos originate in radio-bright galaxies. The significance of the correlation and its physical origin, if any, 69 are debated.…”
Section: The Blueprint Of the Txs 0506+056 Beam Dump?mentioning
confidence: 99%
“…[3,4] for reviews. Recent studies indicate [5,6] that the entire astrophysical neutrino flux between 1 TeV and 1 PeV, estimated from muon-track events 1) Corresponding author; e-mail: st@ms2.inr.ac.ru and extrapolated to lower energies as a power law [7], may be associated with radio blazars. However, analyses of cascade events [8] indicate that this extrapolation may underestimate the flux at several tens TeV.…”
mentioning
confidence: 99%